Establishment of Genetic Transformation System in Napiergrass (Pennisetum purpureum Schumach) - Umami, N.; Gondo, T.; Ishigaki, G.; Akashi, R. (Faculty of Animal Sciences Universitas Gadjah Mada, 2014)
We have established a transformation protocol for the warm season grasses, Napiergrass (Pennisetum purpureum Schumach). A vector containing a herbicide resistance gene (bar) together with the GUS reporter gene (pAHC25) was used in transformation experiments using particle inflow gun-mediated gene transfer. The bar gene confers resistance to the herbicide bialaphos. The selected genotype was cultured in an improved culture system and regenerative callus was produced on medium DBCH-MS medium with 50 μM CuSO4 content at elevated temperature and in the light condition. Explant of Dwarf Napiergrass was inducted 35% embryogenic callus. Embryogenic callus as target tissue by the osmotic process using sorbitol ).3M and mannitol 0.3 M produced high number of GUS gene expression. Regenerated plant were able to confirm transgene. All green herbicide-resistant regenerants were morphological normal in the soil media. This study is the first report of using selection of GUS expression to procure transgenic Napiergrass. In the future, GUS gene will be co-bombarded with candidate genes to produce Napiergrass with improved or novel properties.